Analysis of the Application of the Canvas Business Model to Generation Z Micro Entrepreneurs (Analysis of the Application of the Canvas Model to Generation Z Micro Entrepreneurs) - Fajar Aulia Jar (Takaza Innovatix Labs Ltd., 2026)
This study investigates the application of the Business Model Canvas (BMC) to micro-businesses operated by Generation Z entrepreneurs. Employing a descriptive survey methodology, the research collected data from 10 online micro-entrepreneurs through questionnaires. The results revealed that 83% of respondents positively perceived the use of BMC, suggesting its relevance in guiding strategic planning and operational effectiveness. The study contributes a structured model that maps nine key BMC elements to the digital habits and needs of Gen Z entrepreneurs. The findings highlight how BMC enhances business clarity, internal coordination, and motivation.